Perlindungan hukum terhadap korban tindak pidana rekayasa foto yang melanggar kesusilaan - Hafid, Abdul (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
One of the crimes committed by misusing computer technology is manipulating a person's photo into a photo that contains elements of defamation. A person's photo can be altered using software that is part of technological sophistication, so that the photo contains elements of defamation. The purpose of this study is to examine and analyze legal elements and to examine and analyze legal protection provisions for victims of criminal acts of photo manipulation that violate decency as regulated in Article 27 of Law No. 11 of 2008 concerning Electronic Information and Transactions in conjunction with Article 282 of Law No. 1 of 1946 concerning Criminal Law Regulations in accordance with human needs as stipulated in the Human Rights Law. This research is normative in nature and uses a regulatory approach. The research approach uses three interpretations, namely grammatical interpretation, authentic interpretation, and systematic interpretation. The research found that (1) the act of manipulating a person's photo displayed on the internet is a new type of crime in line with technological developments. (2) Legal actions that can be taken by victims of photo manipulation crimes on the internet include civil lawsuits and criminal charges. Criminally, victims can refer to the provisions set forth in Article 45 paragraph (1) of Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE).